The association between caffeine and cognitive decline: examining alternative causal hypotheses. (April 2014) - Ritchie, K.; Ancelin, M.L.; Amieva, H.; Rouaud, O.; Carrière, I.
ABSTRACT Background: Numerous studies suggest that higher coffee consumption may reduce the rate of aging-related cognitive decline in women. It is thus potentially a cheap and widely available candidate for prevention programs provided its mechanism may be adequately understood. The assumed effect is that of reduced amyloid deposition, however, alternative pathways notably by reducing depression and diabetes type 2 risk have not been considered. Methods: A population study of 1, 193 elderly persons examining depressive symptomatology, caffeine consumption, fasting glucose levels, type 2 diabetes onset, serum amyloid, and factors known to affect cognitive performance was used to explore alternative causal models. Results: Higher caffeine consumption was found to be associated with decreased risk of incident diabetes in men (HR = 0.64; 95% CI 0.42–0.97) and increased risk in women (HR = 1.51; 95% CI 1.08–2.11). No association was found with incident depression. While in the total sample lower ratio Aβ42/Aβ40 levels (OR = 1.36, 95% CI 1.05–1.77, p = 0.02) were found in high caffeine consumers, this failed to reach significance when the analyses were stratified by gender. Conclusions: We found no evidence that reduced risk of cognitive decline in women with high caffeine consumption is moderated or confounded by diabetes or depression. The evidence of an association with plasma beta amyloid could not be clearly demonstrated. Insufficient proof of causal mechanisms currently precludes the recommendation of coffee consumption as a public health measure. Further research should focus on the high estrogen content of coffee as a plausible alternative explanation.